2015
DOI: 10.15760/honors.190
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Suicidal Ideation in Undergraduate College Students: Risk Factors and Barriers to Treatment Present Within Universities

Abstract: Writing and research on depression and suicidal ideation for this undergraduate thesis has been a unique and treasured learning experience made possible by many individuals. I would like to thank my thesis advisor, Dr. Tina Burdsall, for her outstanding guidance and support in my efforts. I would also like to thank Dr. Ann Marie Fallon, who has shared her knowledge and guidance with me throughout my entire undergraduate career. Additionally, I would like to thank the Portland State Honors College and my honors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(73 reference statements)
1
2
0
Order By: Relevance
“…[ 23 ] This can be explained by the bi-directional association between depression and academic performance. [ 24 , 25 ] The study in India also supported the association observed between substance abuse and depression among the student in the current study. [ 26 ] Low quality of food and monetary issues are more often seen in students of parents with lower socioeconomic status and those residing at the hostel, which is associated with depressive symptoms in students.…”
Section: Discussionsupporting
confidence: 82%
“…[ 23 ] This can be explained by the bi-directional association between depression and academic performance. [ 24 , 25 ] The study in India also supported the association observed between substance abuse and depression among the student in the current study. [ 26 ] Low quality of food and monetary issues are more often seen in students of parents with lower socioeconomic status and those residing at the hostel, which is associated with depressive symptoms in students.…”
Section: Discussionsupporting
confidence: 82%
“…Various studies found that depression deteriorates cognitive functioning like memory, attention, concentration, abstract reasoning, and judgment which trigger the students to achieve poor academic activities. in another pole students with poor academic status will be tensioned, worried, and end up with substances for improving their concentration, which can ultimately lead them to have depression [26,78].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of negative effects on the mental health of these individual has caused the IGD as a matter that researchers need to pay attention to (APA, 2013). This is because when individuals with depression are potentially able to do things that can harm themselves including having the idea of committing suicide-related behavior (Roesch, 2015). Based on Ko et al (2021), although the existence of suicidal ideation is closely related to suicide attempts, but not all those who have suicidal ideation will attempt to commit suicide.…”
Section: Introductionmentioning
confidence: 99%